INTEREST OF VOCATIONAL SCHOOL STUDENTS IN THE SELECTION OF BUILDING ENGINEERING STUDY PROGRAM PALANGKA RAYA UNIVERSITY IN CLASS XII OF SMK N 1 PALANGKA RAYA - David Pratama Putra; Wiratno; Revianti Coenraad (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2021)
This study is descriptive research with a quantitative approach, the research subjects as many as 131 students from 7 different skill program classes in class XII SMK N 1 Palangka Raya. The questionnaire uses a likert scale and is created in the form of a Google form, then distributed online to students. After that, the data is analyzed using the achievement degree formula (DP) and multiple linear regression analysis. The results showed that the average percentage of interest of students of SMK N 1 Palangka Raya towards the selection of Program Building Engineering Education Study of Palangka Raya University amounted to 72.67% and belonged to the category of quite in demand. While the factors that affect the interest of students of SMK N 1 Palangka Raya continue their studies in the Building Engineering Education Study Program of The University of Palangka Raya, namely self-motivation factors, opportunity factors, social environmental factors and institutional factors are simultaneously indicated with a significance value of less than 0.05 and Fcalculated greater than Ftable (41,898 > 2.44). The most partially significant factor is the institutional factor with tcalculated value greater than the ttable value (7.605 > 1.97897). This research can be developed again, considering that only 55.7% of the free variables discussed in this study are able to explain bound variables,in addition this study can be used as an evaluation material on improving the promotion of PTB UPR Study Program